Educação e família - Delmond, Gisselly Vieira Souza (2015)
This work is part of a line of research Fundamentals of Educational Processes of PPGE/FE/UFG and objective, through literature, understand the relationship between family and education from the perspective of socialization processes. From this perspective, from the contribution of Freud, especially the processes of repression and identification, is analyzed as the family mediation which constitutes between nature and culture, it is fundamental in the constitution of the subject. The family as a necessary mediation of the formation of subjectivity has undergone changes in its dynamics and structure, which implies new forms of subjectivity, from which derive new challenges to contemporary educational processes. Understand the educational function of the family and its historical, objective and subjective specific calls into question the challenges, conditions and opportunities for an education that posits the autonomy and emancipation.